Report of the United Nations Commission on International Trade Law - United Nations Department for General Assembly; Conference Management (United Nations, 2024)
This annual report of the United Nations Committee on International Trade Law (UNCITRAL) submitted to the General Assembly covers the Fifty-seventh session (24 June–12 July 2024).